THE ROLE OF CYTOLOGICAL AND VIROLOGICAL STUDIES IN SECONDARY PREVENTION OF CERVICAL CANCER - E. V. Bahidze (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. This article is devoted to the role of cytological and virological screening in the secondary prevention of cervical cancer. Five hundred and fifty two cases of carcinoma in situ (of cervical cancer) and 1248 cases of invasive cervical cancer over a period of 15 years were analyzed. This period has separated into three stages: I — 1998–2002, II — 2003–2007, III — 2008–2012 years. Cervical cancer morbidity in Karelia is reported to increase tripled from 10.5 to 30.5 causes per 100 thousand women population. The excess incidence has identified among young women in reproductive age including an age group < 30 year. It has been noticed that the detection rate of carcinoma in situ was statistically significant increased from 24.34±9.2% in 1998–2002 to 62.8±20.9% in 2008–2012 years. There are three different level regional groups of early cervical cancer detection (0–I–II stage) in the Republic of Karelia. Despite of the fact, that the cervical cancer is increas-ing significantly, there are a good results of its early diagnostics, thanking to the cytological and virological screening in Karelia.